2014
DOI: 10.1016/j.molonc.2014.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Combination of novel HER2‐targeting antibody 1E11 with trastuzumab shows synergistic antitumor activity in HER2‐positive gastric cancer

Abstract: The synergistic interaction of two antibodies targeting the same protein could be developed as an effective anti-cancer therapy. Human epidermal growth factor receptor 2 (HER2) is overexpressed in 20-25% of breast and gastric cancer patients, and HER2-targeted antibody therapy using trastuzumab is effective in many of these patients. Nonetheless, improving therapeutic efficacy and patient survival is important, particularly in patients with HER2-positive gastric cancer. Here, we describe the development of 1E1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…The antigen binding site is an intrinsic characteristic of therapeutic antibodies and the basis for conjugation with chemotherapeutic agents or drugs. 22,42 In the current study, we found that the hertuzumab targeted epitope was distinct from the epitope recognized by trastuzumab. We also found the affinity between HER2 and hertuzumab was higher than that of trastuzumab.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The antigen binding site is an intrinsic characteristic of therapeutic antibodies and the basis for conjugation with chemotherapeutic agents or drugs. 22,42 In the current study, we found that the hertuzumab targeted epitope was distinct from the epitope recognized by trastuzumab. We also found the affinity between HER2 and hertuzumab was higher than that of trastuzumab.…”
Section: Discussionmentioning
confidence: 57%
“…[16][17][18][19][20][21] Combination of trastuzumab with another HER2 targeting monoclonal antibody also showed synergistic antitumor activity in HER2-positive gastric cancer. 22 Thus, targeted HER2 therapy in gastric cancer is effective, although there is still a large percentage of patients with HER2-positive gastric or breast cancer presenting with a clinical resistance to trastuzumab. 17,23,24 Furthermore, the antibody-drug conjugate (ADC) is a novel class of targeting antitumor therapy that is more effective than antibodies alone and has fewer side effects, which may be due to a low concentration of free chemotherapeutic drug in the host blood system.…”
Section: Introductionmentioning
confidence: 99%
“…Afatinib in combination with trastuzumab appears to be promising in heavily pretreated HER2+ patients, with a disease control rate of 42% at 4 months with single agent afatinib 77 and the combination cohort ongoing. 1E11, a novel humanized monoclonal antibody that targets HER2, has been shown to have synergistic activity with trastuzumab in HER2 overexpressing gastric cancer cell lines 78 . Recently, a new anti-HER2 antibody with optimized Fc-receptor binding affinity has entered phase II of clinical testing in combination with anti-PD1 antibody pembrolizumab in advanced metastatic gastric and GEJ adenocarcinoma (NCT02689284, clinicaltrials.gov ).…”
Section: Targeting Her2: Antibodies Drug Positivity Conjugates Amentioning
confidence: 99%
“…The in vitro anti-proliferative activities of hz1E11 as a single agent and in combination with trastuzumab were also equivalent to those of ch1E11 ( Fig 2C ). In the previous study [ 22 ] it was reported that ch1E11 had in vivo antitumor activity comparable to that of trastuzumab as a single agent, and the combination of ch1E11 and trastuzumab resulted in the tumor regression index (TGI) of 95.1%. Similarly, hz1E11 as a single agent had similar in vivo antitumor activity to trastuzumab ( S1 Fig ) and the combination of hz1E11 with trastuzumab also showed dose-dependent anti-tumor activity in the NCI-N87 xenograft mouse model ( Fig 2D ).…”
Section: Resultsmentioning
confidence: 99%
“…We previously developed a murine antibody targeting HER2 (clone 1E11) that shows synergistic antitumor activity in combination with trastuzumab in HER2 overexpressing gastric cancer cell lines [ 22 ]. In this report, we describe how we optimized the 1E11 for a therapeutic antibody by CDR grafting to human germline immunoglobulin variable genes and affinity maturation through targeted randomization of CDR-H3 and CDR-L3.…”
Section: Introductionmentioning
confidence: 99%